Pengaruh Service Quality, Information Quality, Sistem Quality Terhadap Net Benefit Mediasi User Satisfaction Dan Intention Use - Nugraha, Aprian; Yustini, Tien (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study was to determine the effect of Service Quality, Information Quality, System Quality on Net Benefit Mediation Customer Trust and Intention Use (Case Study on Mobile BNI Banking Prabumulih Branch). This research method uses a descriptive survey and verification, field data collection using questionnaire techniques, interviews and documentation. This research is associative research, where in this study there are variables that are related and can affect other variables. affect other variables. The population of this research is Bank BNI Branch customers Prabumulih. With incidental method sample method with a sample size of 111 respondents. Data processing using Smart analysis tool PLS v 3 The results of the study concluded that 1). Information Quality does not positive and insignificant effect on Net Benefit 2). Information Quality has no positive and insignificant effect to Use 3).Information Quality has no positive and insignificant effect on User Satisfaction 4). Service Quality has a positive and significant to Net Benefit 5) Service Quality has a positive and significant effect on Use 6).significant on Use 6). Service Quality has a positive and significant on User Satisfaction 7). System Quality has no positive and insignificant effect to Net Benefit 8). System Quality has no positive and insignificant effect to Use. 9) System Quality has no positive and insignificant effect on User System Quality has no positive and insignificant effect on User Satisfaction 11). User Satisfaction has a positive and significant effect on Net Benefit.